Application of Pancasila Values in Intra-School Student Organization Activities - Ibnu Farih Sunanta Batubara (International Journal of Students Education, 2024)
This research uses a literature review method to investigate related themes in a particular field of study. This approach allows researchers to investigate and evaluate various points of view, findings, and arguments that have been put forward by previous researchers, as well as identify knowledge gaps that still exist in this field of study. The aim of this research is to collect, analyze and synthesize relevant literature in order to gain an in- depth understanding of the topic under study. Through the steps of identifying relevant sources, critical analysis of existing literature, and synthesis of important findings, this research produces a comprehensive understanding of the latest developments in the field of study. The findings of this research present various points of view, arguments and findings that have been put forward by previous researchers, as well as identifying knowledge gaps that still need to be explored further. The results of this study provide a strong basis for forming conclusions and recommend future research directions in this area.